Biocompatible Hermetic Encapsulation for Implantable Miniaturized Biomedical Sensor System. (2017) - Jorsch, C.; Guenther, M.; Gerlach, G.
Abstract: The field of medical engineering with high standards for implantable applications requires frequently not only sensitive measuring systems but also long term stability and less inflammatory reactions after implantation. Implantable electronics relies on a hermetic and dissolvent consistent encapsulation. Already used materials, such as parylene C, have excellent barrier properties, protect from corrosion and show good bio-stability. But, the biocompatibility of such materials is often insufficient. The in this work described encapsulation with a special coating of polyethylene glycolated amino acids could improve this. The better cell compatibility as well as the protein repellent behaviour and the changes in surface characteristics implies that this coating enhances the functionality and biocompatibility in general. This encapsulation is of current interest for an implantable blood glucose measuring system based on the piezoresistive pressure sensor chip containing a glucose-sensitive hydrogel in its cavity.